Identification of Chemical Constituents of Zingiber zerumbet Rhizome Extract Using GC/MS. Issue 5 (2nd September 2020) - Dash, Biswabhusan; Sahoo, Ambika; Ray, Asit; Jena, Sudipta; Nayak, Sanghamitra
Abstract: Zingiber zerumbet (L.) Roscoe ex Sm. (family-Zingiberaceae) is an important medicinal herb. Though rhizome extract of this species has been used in traditional herbal medicine across the globe for the treatment of numerous diseases like worms, cough, leprosy, asthma and other skin diseases, the composition of the extract is not characterised properly till date. Thus, acetone extract of Zingiber zerumbet rhizome was subjected to Gas Chromatography-Mass Spectrometry (GC/MS) to analyze the phytoconstituents. A total of nine compounds were obtained out of which zerumbone was found to be the major constituent covering 64.58 % of the total area. Beside zerumbone, other important compounds like diacetone alcohol (10.64 %), α-humulene (8.93 %), caryophyllene oxide (5.68 %), humulene epoxide (3.18 %), Eudesm-7(11)-en-4-ol (2.87 %), aromadendrene oxide (1.98 %) were also found in the tested extract with some other compounds in trace amount. Among the compounds, terpenes were found to be the primary constituent of the extract. This finding revealed the presence of the high amount of terpenes in the rhizome of Z. zerumbet for the first time. The study indicated that Z. zerumbet is a good source of sesquiterpenes and oxygenated sesquiterpenes which can be used at industrial level for the production of pharmaceuticals, perfumes and flavouring agents.